Back Cover: Picoscale Magnetoelasticity Governs Heterogeneous Magnetic Domains in a Noncentrosymmetric Ferromagnetic Weyl Semimetal (Adv. Quantum Technol. 3/2021). Issue 3 (15th March 2021) - Xu, Bochao; Franklin, Jacob; Jayacody, Amani; Yang, Hung‐Yu; Tafti, Fazel; Sochnikov, Ilya
Abstract : Shown on the cover illustration is a scanning Superconducting QUantum Interference Device (SQUID) susceptometer. Its exclusive microscopy capabilities were used to image the surface of a magnetic Weyl semimetal. Magnetism was found to be influenced by small internal strains which resulted in two distinct types of large magnetic domains: ferromagnetic and metastable. These results can guide future efforts in building practical devices from topological materials for quantum sensing applications. For further details see article number 2000101 by Ilya Sochnikov and co‐workers.